STUDY ON THE IMPLEMENTATION OF THE BALANCE FUND POLICY AND ITS IMPLICATIONS ON THE MINIMUM SERVICE STANDARDS FOR SUSTAINABLE DEVELOPMENT IN THE CITY OF PEKANBARU - Fendri Jaswir; Sufian Hamim; Rahyunir Rauf (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The purpose of this study is to Analyzing and Explaining the Implementation of the Balanced Fund Policy Its Implications on the Minimum Service Standards for Sustainable Development in the City of Pekanbaru. This research uses the theory of the implementation of Edward III's policy and Government Regulation Number 2 of 2018 concerning Minimum Service Standards and Minister of Home Affairs Regulation Number 100 of 2018 concerning the Implementation of Minimum Service Standards, as guidelines in the preparation of planning documents in the implementation of SPM in the area of the head office. Therefore, the Development of Competence in the Preparation of Planning Documents in terms of the implementation of SPM in the Scope of the Head Office area will provide a clear overview of the vision, mission, goals and strategies as well as the direction of regional development policies as well as the minimum service standards that have been promised to the community." Minimum Service Standards (SPM) is a provision regarding the type and quality of basic services which are Mandatory Government Affairs that every citizen is entitled to obtain at a minimum. SPM is determined and applied based on the principles of conformity of authority, availability, affordability, sustainability, measurability and accuracy of targets". The nature of this research is qualitative with an analytical descriptive type. The number of informants was 27 people through purposive sampling techniques. Data collection techniques with interviews and observations. The policy facilitates the allocation of central government funds to local authorities, enabling improvements in essential public services such as education, health, infrastructure, and social welfare. However, the effectiveness of this policy is contingent upon the capacity of local institutions to manage funds efficiently, coordinate inter-agency efforts, and align planning with regulatory requirements. Challenges including administrative constraints, delayed disbursements, and limited community engagement have impacted the full realization of service standards. Nevertheless, when effectively implemented, the Balance Fund Policy contributes significantly to enhancing service availability, equity, and quality, which are foundational for sustainable urban development.